Internationalizing R&D Co-opetition: Dress for the Dance with the Devil - Anja Schmiele; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Competitors can be valuable sources and partners for innovation activities. Against the background of international expansion of firms and increased international competition, the R&D collaborations with international competitors (international co-opetition) is becoming an increasingly interesting way to gain access to well guarded knowledge from abroad. However, to be able to benefit from these paradox alliances, a certain level of international co-opetition readiness is required. On the one hand, this readiness is important to protect the companies? intellectual property that should not be leaked to competitors. On the other hand, the firm has to be able to absorb and utilize the knowledge and capabilities of the collaborating competitor. Hence, we envision co-opetition as a balancing act between appropriability practices and absorptive capacities in a cross-border context. We test these dual hypotheses for a broad sample of roughly 1,000 innovative firms in the German manufacturing sector. We find that co-opetition with international competitors requires a shift in appropriability practices from informal methods (secrecy, lead time) towards formal ones (like patents and copyrights). Besides, we discover that the readiness for international co-opetition can be achieved by developing international collaboration experience through collaborations with international customers or suppliers.
Keywords: D83; O32; O31; F23; 330; Co-opetition; R&D collaboration; internationalization; innovation management; Industrielle Forschung; Forschungskooperation; Coopetition; Multinationales Unternehmen; Lieferanten-Kunden-Beziehung; Lernprozess; Deutschland